Construction of a High-Density Genetic Map and Its Application for QTL Mapping of Leaflet Shapes in Mung Bean (Vigna radiata L.) - Wang, Jie; Li, Jianling; Liu, Zhenxing; Yuan, Xingxing; Wang, Suhua; Chen, Honglin; Chen, Xin; Cheng, Xuzhen; Wang, Lixia (Frontiers in Genetics, 2020)
Mung bean (Vigna radiata L.) is an important but understudied food legume in Asia and now worldwide. Genetic study studies may help tocould accelerate the exploitation of new genes for breeding in this crop. In the present studyHere, we used a recombination inbred line (RIL) population to construct an SNP genetic linkage map by genome sequencing technology. We obtained 21508 high quality SNP markers and The result showed that a total of 6745 high quality SNP markers were developed and 1946 bin markers that were mapped onto 11 linkage groups (LGs) with 99-258 bin markers per LG. The number of bin markers per LG ranged from 99 to 258. The total genetic length of the map was 1060.2 cM, ranging from( 38.76 cM to -168.03 cM per LG), with an average distance between markers of 0.54 cM. However there were 18 gaps >5cM, distribution on LG1, 3, 5, 7 and 9. Gene mapping for lobed and indented leaflets, were conducted using the map. A major QTL associated with indented leaflets was detected on chromosome 10, with phenotypic variation explained values of 39.7% and 45.4% of phenotypic variation explanation under two different environments. SFor lobed leaflets, several QTLs For lobed leaflets were detected, and most of them were tightly linked togetherlocated on Chromosome 3 by clusters, . but However, only one major QTL, which explaining explained the largest phenotypic variationPVE (28.37.7%-69.5%), was stably detected under two different environments using both using R and Q methods. Within In the two main stable major QTLs regions on chromosomes 3 and 10, candidate genes for regulating the molecular mechanism of different leaflet shapes were predicted detected through by functional annotation. The overlap of major QTLs under different environments indicated that the present map would be good enough for precisely mapping genes, while and both the QTL analysis and gene prediction would be the were useful for investigating the mechanism of leaf development in mung bean or legumes.